Signage and wayfinding in library planning and design / Ahmad Zulhilmi Azmi and Rosidah Ismail - Azmi, Ahmad Zulhilmi; Ismail, Rosidah (2014)
This article discusses the importance of signage and wayfinding in library planning and design. The bigger the library, the need for good signage and wayfinding system increase. Signage is a library's basic link to users. This is true whether the sign's purpose is to promote impulse "stop and use," to create awareness for the product or service for future reference.